A new species of Cypris (Crustacea: Ostracoda) from the Iberian Peninsula and the Balearic Islands, with comments on the first ostracod named using the Linnean system - Mesquita-Joanes, Francesc; Aguilar-Alberola, Josep A.; Palero, Ferran; Rueda, Juan (Zootaxa, 2020)
The genus Cypris, considered the oldest ostracod generic name erected using the Linnean system, comprises a reduced number of large-bodied species, mostly found in Africa and Asia. Only six of them are known to occur in Europe. Here we describe a new species, Cypris pretusi sp. nov., collected in small temporary streams and ponds along the Eastern Iberian Peninsula and Minorca (Balearic Islands). The new species is very close to the type species of the genus, Cypris pubera O.F. Müller, 1776, but differs from it in having a set of smaller subequal spines on the posterior edge of the valves, by the absence of conspicuous spines along the front edge, and by the beak-like frontal shape of its carapace in dorsal view, similar to Cypris decaryi Gauthier, 1933. Soft parts are very similar to the type species, but it differs in having shorter swimming setae on the second antennae. Molecular analyses of the COX1 region support its status as a species distinct from C. pubera and closer to Cypris bispinosa Lucas, 1849, also providing evidence for a separation of C. pubera s.l. in two clades, one of which is here considered to correspond to Cypris triaculeata Daday, 1892. We discuss the relationships of C. pretusi sp. nov. to other members of the genus and its possible origin from nearby biogeographic regions (probably Africa or Asia) and provide a key to species of Cypris found in Europe. We also discuss the relationship between Monoculus concha pedata (= M. conchaceus), the first ostracod named by Linnæus, and Cypris pubera, the type species of the genus, described by Müller in 1776 and considered by him the same species as the one first named by Linnæus.